Towards a Sustainable Vector-Control Strategy in the Post Kala-Azar Elimination Era - Garlapati, Rajesh; Iniguez, Eva; Serafim, Tiago D.; Mishra, Prabhas K.; Rooj, Basab; Sinha, Bikas; Valenzuela, Jesus G.; Srikantiah, Sridhar; Bern, Caryn; Kamhawi, Shaden (Frontiers in Cellular and Infection Microbiology, 2021)
Visceral leishmaniasis (VL) is a potentially deadly parasitic disease. In the Indian sub-continent, VL is caused by Leishmania donovani and transmitted via the bite of an infected Phlebotomus argentipes female sand fly, the only competent vector species in the region. The highest disease burden is in the northern part of the Indian sub-continent, especially in the state of Bihar. India, Bangladesh and Nepal embarked on an initiative, coordinated by World Health Organization, to eliminate VL as a public health problem by the year 2020. The main goal is to reduce VL incidence below 1 case per 10,000 people through early case-detection, prompt diagnosis and treatment, and reduction of transmission using vector control measures. Indoor residual spraying, a major pillar of the elimination program, is the only vector control strategy used by the government of India. Though India is close to its VL elimination target, important aspects of vector bionomics and sand fly transmission dynamics are yet to be determined. To achieve sustained elimination and to prevent a resurgence of VL, knowledge gaps in vector biology and behavior, and the constraints they may pose to current vector control methods, need to be addressed. Herein, we discuss the successes and failures of previous and current vector-control strategies implemented to combat kala-azar in Bihar, India, and identify gaps in our understanding of vector transmission towards development of innovative tools to ensure sustained vector control in the post-elimination period.